Discovery of highly potent and selective orexin 1 receptor antagonists (1-SORAs) suitable for in vivo interrogation of orexin 1 receptor pharmacology. Issue 23 (1st December 2016) - Stump, Craig A.; Cooke, Andrew J.; Bruno, Joseph; Cabalu, Tamara D.; Gotter, Anthony L.; Harell, C. Meacham; Kuduk, Scott D.; McDonald, Terrence P.; O'Brien, Julie; Renger, John J.; Williams, Peter D.; Winrow, Christopher J.; et al.
Graphical abstract: Abstract: While a correlation between blockade of the orexin 2 receptor (OX2 R) with either a dual orexin receptor antagonist (DORA) or a selective orexin 2 receptor antagonist (2-SORA) and a decrease of wakefulness is well established, less is known about selective blockade of the orexin 1 receptor (OX1 R). Therefore, a highly selective orexin 1 antagonist (1-SORA) with suitable properties to allow in vivo interrogation of OX1 R specific pharmacology in preclinical species remains an attractive target. Herein, we describe the discovery of an optimized 1-SORA series in the piperidine ether class. Notably, a 4, 4-difluoropiperidine core coupled with a 2-quinoline ether linkage provides OX1 R selective compounds. The combination with an azabenzimidazole or imidazopyridine amide substituent leads to analogs47 and51 with >625-fold functional selectivity for OX1 R over OX2 R in rat. Compounds47 and51 possess clean off-target profiles and the required pharmacokinetic and physical properties to be useful as 1-SORA tool compounds.